Impact of a Low-Permeability Layer on the Pumping Efficiency Under Threats of Saltwater Up-Coning - Wu, Zhenyu; Tang, Maozhu; Daly, Edoardo; Lu, Chunhui (Frontiers in Environmental Science, 2022)
Previous studies on saltwater up-coning are mostly based on the assumption of a homogeneous aquifer and neglect the effect of heterogeneity. A numerical study was carried out to explore the impact of a low-permeability (k) layer on the pumping efficiency under threats of saltwater up-coning. It is found that the presence of the low-k layer could impede up-coning of saltwater, thereby improving significantly pumping efficiency, as expected. For the cases adopted, when the permeability of the 2 m thick low-k layer is three orders of magnitude less than that of the corresponding homogeneous aquifer, the pumping duration (i.e., the time before the salinity of pumped water reaches 2%) can be up to about 10 times longer than that of the homogeneous aquifer case. Additionally, a sound linear relationship could be developed between the normalized pumping duration of the layered case (E) (defined as the difference of the pumping duration between layered and homogeneous cases relative to the pumping duration in the homogeneous case) and the permeability of the homogeneous aquifer relative to that of the low-k layer (β). However, a short low-k layer may lead to the failure of this linear relationship. Moreover, a thicker low-k layer leads to a larger E when all other conditions are unchanged. When varying the location of the low-k layer, the large E occurs for the low-k layer located below and near the well bottom. The results obtained in the current study offer significant implications for preventing saltwater up-coning and improving the pumping efficiency through natural and artificial barriers.